Relationship Marketing: the use of digital strategies in dentistry - Diego Anselmi Pires; Izandra Maria da Silva Leandro; Rafaela da Rosa Camargo; Magada Tessman Schwalm (Associação Brasileira de Odontologia, 2018)
Objective: to analyze the digital strategies known and used by Dental Surgeons in relation to Relationship Marketing. Material and Methods: this is a quantitative, descriptive, documentary, field and cross-sectional research. The research was performed through a standard e-mail sent to Dental Surgeons of the State of Santa Catarina, containing a link to the questionnaire and the Informed Consent Term. Results: after the data collection period, 31 electronic questionnaires answered by the Dental Surgeons were analyzed, outlining a predominant profile of the study participants containing more often young, white and single women, with some type of post-graduation, varying from 1 to 4 years of training, generally being owners of the place where they work, with more than one employment relationship. The digital strategies most known by the participants were Facebook, WhatsApp, Instagram and Websites. In turn, the most used were Facebook and Instagram, and a significant percentage reported not using any digital strategy. Conclusion: dentists from Santa Catarina presented little knowledge about the definition of Relationship Marketing and digital strategies. Although the most reported digital media have been Facebook and Instagram for the purpose of improvement and communication, the same media have been little used for Relationship Marketing actions.